Re-Writing His-Story: Exploring the Censorship of History through School Textbooks and Public Artefacts (Yesterday & Today Journal for History Education in South Africa and abroad, 2024)
This article, titled Re-writing His-Story: Exploring the censorship of History through school textbooks and public artefacts, explores how ideological and political differences of those in power can censor history, affecting how future generations engage with the past. As new regimes ascend, they promote a distinctive cultural narrative that could alter or omit long-standing historical narratives. Textbooks and historic monuments are cultural artefacts created at a specific time, in a space, and a particular context. In South Africa, for example (as in many other countries), historic monuments and public statues have been (re)moved, and selectively replaced by alternative heroes. Likewise, post-apartheid textbooks have been rewritten to include cultural diversity. Our principal concern is the restricted access to key symbols of the past as future generations lose crucial historical facts and a sense of identity as different histories are propagated. Located in the interpretive paradigm, the study utilises a desktop review incorporating critical discourse analysis to understand how meaning is conveyed about textbooks and public artefacts in print media and online platforms. Using a wide range of case studies as its empirical base, the findings indicate that textbook content is censored due to the influence of socio-political, cultural, and religious reasons. Similarly, monuments, statues, and other public artefacts perceived as outdated or representing controversial histories are often targeted for removal.
Keywords: Censorship; Artefacts; Monuments; Cultural revision; Public statues; Rewriting history; Textbooks